Caminhos da interdisciplinaridade: da formação por área de conhecimento à prática educativa de egressos da licenciatura em educação do Campo-Procampo/IFPA, Campus de Castanhal, PA - Silva, Márcia Cristina Lopes e (2017)
This study aims to analyze the interdisciplinarity through the educational practice of the graduates of the course in Rural Education PROCAMPO-IFPA-Campus of Castanhal - Pará, seeking to understand the formative process from the perspective of the area of knowledge, in the sense of contributing to the Rural Educators. The course has its training based on the area of knowledge chosen by students between Human and Social Sciences or Natural Sciences and Mathematics, according to the area of their interest, from the 5th semester. The frame of reference was based on the conceptual categories: interdisciplinarity, training according to the area of knowledge and educational practice. The research was characterized as qualitative, based on a Case Study. The methodological instruments used were participant observation, semi-structured interviews and collective interview with the research subjects in their bases. The field work was based on the observations of the educational practices of the work with the interdisciplinarity in the schools in which the graduates educators act. That issue is necessary when it comes to the focus of the area of knowledge, which is stressed in the course. They studied the Pedagogical Project of the Course (PPC) and interviewed the teachers and coordinators. The fieldwork was carried out in rural communities and settlements, where the egresses live and work as educators, located in the regions of Amazon in the state of Pará. That region is marked by the diversity of subjects, cultures and knowledge regarding to Rural Education. The studies showed an attempt of interdisciplinarity, both in the educational practices of the teachers, in the training course and of the graduates in their professional actions. This pointed to the need to strengthen the continuing education of the rural education teachers and of the graduates. As a result, research has also signaled to the importance of rebuild the Pedagogical Projects of the Rural Schools, emphasizing the area of knowledge training and the collective work as crucial role in order to contribute to the rural education policies in the region.